Directly probing anisotropy in atom-molecule collisions through quantum scattering resonances - Klein, Ayelet; Shagam, Yuval; Skomorowski, Wojciech; Zuchowski, Piotr S.; Pawlak, Mariusz; Janssen, Liesbeth M. C.; Moiseyev, Nimrod; Van De Meerakker, Sebastiaan Y. T.; Van Der Avoird, Ad; Koch, Christiane P.; Narevicius, Edvardas (Nature Physics, 2017)
Anisotropy is a fundamental property of particle interactions. It occupies a central role in cold and ultracold molecular processes, where orientation-dependent long-range forces have been studied in ultracold polar molecule collisions. In the cold collisions regime, quantization of the intermolecular degrees of freedom leads to quantum scattering resonances. Although these states have been shown to be sensitive to details of the interaction potential, the effect of anisotropy on quantum resonances has so far eluded experimental observation. Here, we directly measure the anisotropy in atom-molecule interactions via quantum resonances by changing the quantum state of the internal molecular rotor. We observe that a quantum scattering resonance at a collision energy of k B × 270 mK appears in the Penning ionization of molecular hydrogen with metastable helium only if the molecule is rotationally excited. We use state-of-the-art ab initio theory to show that control over the rotational state effectively switches the anisotropy on or off, disentangling the isotropic and anisotropic parts of the interaction.
CRIS-Team Scopus Importer:2023-04-20